KUALITAS PELAYANAN PUBLIK DI KELURAHAN MARIANA KECAMATAN PONTIANAK KOTA KOTA PONTIANAK - Antonius Lonti Siron E.01105126 (FISIP Universitas Tanjungpura, 2013)
This article is motivated by wanting to know the quality of the Public Waitress at the Village Office Mariana Pontianak. This writing is intended to solve the problems faced by the Society of related public services. Quality of public services in the Village Mariana conducted based on the real-real services they receive / get with the real services and bottlenecks.Problems that still occur in the service at Marian Village Pontianak is less complete in completing the requirements of the community, as well as the lack of employees at a particular time if the government makes a mass program to serve the community.Keywords: Service Quality, Service Delivery, Service Barriers